Production of “chonto” tomato lines, Solanum lycopersicum Mill., with expression of the sp gene responsible of determinate growth - Burbano E., Esteban; Vallejo C., Franco Alirio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2017)
Introgression of the recessive sp gene, responsible of determinate growth, was carried out from IPA 4 Brazilian tomato to UNAPAL-Maravilla Colombian “chonto” tomato to modify the architecture of the plant and contribute to the reduction of production costs. In the F2 generation of the fourth backcrossing, the selection of plants with a height of less than 150 cm, a fruit weight of more than 90 g and an oblate fruit shape was carried out. After the selection process, six lines of tomato “chonto” with a determinate growth habit and characteristics of this type of tomato were evaluated. The D5 and D6 lines with determinate growth were selected, with a plant height of 109.30 and 114.40 cm, harvest days of 87.75 and 87.25, and yield per plant of 4,116.6 and 4,029.7 g, respectively.